Evaluación de modelos digitales de elevación (DEMS) mediante geomorfología tectónica: ejemplo de la Cuenca Moyobamba - Vidal Villalobos, Raul Andres (2022)
Digital elevation models (DEMs) are used recurrently to obtain geomorphological information with which interpretations are made regarding the tectonic evolution of a region. Most studies evaluating the accuracy of these DEMs focus on comparison with terrestrial GPS datapoints and other vertical and horizontal accuracy references. Nevertheless, few studies have used geomorphological analysis for DEM validation, and none have been carried out in Peru. This study seeks to evaluate the performance of free access DEMs with 1 arc-second (30 m) resolution: SRTM3, ASTER GDEM3, ALOS World 3D 30m (AW3D30), Copernicus DEM, and the 0.4 arcsecond (12 m) commercial DEM TanDEM-X. The analyses applied in the present study were channel profile analysis and hypsometry. These were applied in the region of the Moyobamba watershed, a tectonically active piggyback basin, on three different scales: the complete basin, the sub-basins of the tributaries and the individual tributary rivers, separated into steady-state segments when necessary. At the scale of the complete basin channel profile analysis gave solid results regardless of the DEMs. Copernicus DEM has the least amount of error due to its river flow corrections. However, at the level of sub-basins and individual rivers AW3D30 shows less noise in high slope tributaries and shows less variability in the concavity index. ASTER GDEM3 had the worst performance on each scale of analysis. Hypsometry results did not vary significantly between DEMs.